4‐Hydroxynonenal (HNE), a Toxic Aldehyde in French Fries from Fast Food Restaurants. (21st September 2015) - Csallany, A. Saari; Han, I.; Shoeman, D. W.; Chen, C.; Yuan, Jieyao
Abstract: The toxic lipid peroxidation product, α, β, 4‐hydroxy‐2‐ trans ‐nonenal (HNE) concentration, was measured in French fries (FF) from six local fast food restaurants. FF were purchased between 2 and 3 pm from all six restaurants. FF were also purchased at 12, 2, 4, 6 pm from one and at 1, 3, 5, 7 pm from another restaurant. Samples were analyzed for total fat, fatty acid distribution and for HNE by high performance liquid chromatography (HPLC). HNE was confirmed by HPLC/MS. HNE concentrations in FF from the 6 fast food restaurants were between 7.83 and 32.15 µg HNE/100 g FF and between 0.9 and 4.9 µg HNE/g extracted fat. HNE concentrations in FF purchased at 12, 2, 4, 6 pm were between 19.07 and 32.15 µg/g of FF and purchased at 1, 3, 5, 7 pm were between 7.47 and 10.21 µg HNE/100 g of FF. Differences in FA distribution were observed in the samples from some restaurants. FF which contained higher levels of linoleic acid (LA) also contained more HNE. It is clear that HNE is produced during the heating process of the frying oils and is incorporated into FF. Frequently consumed foods containing considerable amounts of HNE, a toxic aldehyde, may be a public health concern since HNE toxicity is related to a number of common pathological conditions.